2021
DOI: 10.1055/a-1478-4574
|View full text |Cite
|
Sign up to set email alerts
|

5-HTTLPR-rs25531 and Antidepressant Treatment Outcomes in Korean Patients with Major Depression

Abstract: Introduction Despite the ethnic differences in 5-HTTLPR (S allele relates to better antidepressant response in Korean and Japanese people, while L allele with better response in Caucasians), it is unclear whether 5-HTTLPR and its high expression locus rs25531 are interactively associated with antidepressant treatment outcome. We investigated the individual and interaction effects of these polymorphisms on antidepressant treatment outcomes in the Korean population. Methods A total of 464 Korean subjects with ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…SERT is encoded by a gene (also known as the solute carrier family 6 member 4, SLC6A4 ) located on chromosome 17q11.2 [ 22 ]. Genetic variants within the promoter of this gene (i.e., rs25531 and rs25532) along with variable number tandem repeat (VNTR) polymorphisms in the promoter and intron 2 regions (5HTTLPR and STin2) modulate its transcriptional activity [ 23 ], influencing emotional, endocrine, and personality characteristics as well as vulnerability to a broad range of psychiatric disorders [ 24 , 25 , 26 , 27 ]. In this scenario, in vivo study demonstrated that transgenic mice overexpressing SLC6A4 are lighter and shorter than controls [ 28 ]; on the other hand, Slc6a4 knockout mice develop late-onset obesity, hepatic steatosis, glucose intolerance, and insulin resistance [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…SERT is encoded by a gene (also known as the solute carrier family 6 member 4, SLC6A4 ) located on chromosome 17q11.2 [ 22 ]. Genetic variants within the promoter of this gene (i.e., rs25531 and rs25532) along with variable number tandem repeat (VNTR) polymorphisms in the promoter and intron 2 regions (5HTTLPR and STin2) modulate its transcriptional activity [ 23 ], influencing emotional, endocrine, and personality characteristics as well as vulnerability to a broad range of psychiatric disorders [ 24 , 25 , 26 , 27 ]. In this scenario, in vivo study demonstrated that transgenic mice overexpressing SLC6A4 are lighter and shorter than controls [ 28 ]; on the other hand, Slc6a4 knockout mice develop late-onset obesity, hepatic steatosis, glucose intolerance, and insulin resistance [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serotonin Transporter Linked-Polymorphic Region (5-HTTLPR), located at the promoter region of the SLC6A4 gene, is one of the most investigated polymorphisms [16], which was discovered to affect the transcriptional activity of serotonin and regulate its expression [17]. There is some evidence that the 5-HTTLPR genotype affects vulnerability to a broad range of psychiatric disorders including depression [18], panic disorder (PD) [19], post-traumatic stress disorder (PTSD) [20], and so forth. While few studies have been performed in ED patients.…”
Section: Introductionmentioning
confidence: 99%
“…Serotonin Transporter Linked-Polymorphic Region (5-HTTLPR), located at the promoter region of the SLC6A4 gene, is one of the most investigated polymorphisms [14], which was discovered to impact the transcriptional activity of serotonin and regulate its expression [15]. There is some evidence that the 5-HTTLPR genotype affects vulnerability to a broad range of mental disorders including depression [16], panic disorder (PD) [17], post-traumatic stress disorder (PTSD) [18], and so forth. However, scarce studies have been performed in ED patients and longitudinal studies in AN have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%